Relationship of ISO 9001:2000 quality system certification with operational and businessperformance: A survey in Australia and New Zealand-based manufacturing and service companies - Feng, M.; Terziovski, Milé; Samson, D. (Emerald Group Publishing Limited, 2008)
Purpose – This research paper aims to explore the relationship between ISO 9000 certification andorganisational performance by developing an ISO 9000 relationship model.Design/methodology/approach – A survey instrument was used for quantitative data collectionbased on a global survey in collaboration with the Anderson School of Business, UCLA. All items weremeasured on a five point modified Likert scale. The data were analysed statistically by means ofStatistical Package for Social Scientists. Factor analysis was performed. Multiple regressions was usedto test the hypotheses. Both validity and reliability of the measures were checked in order to reducemeasurement error.Findings – The results show a positive and significant relationship between certification practices(implementation, organisational commitment and planning) with operational performance. However,the relationship between these practices with business performance was found to be positive but notsignificant of the variables we studied, organisational commitment to certification was found to bemost strongly related to operational and business performance.Practical implications – The success of implementing ISO 9000 certification would be increased(operational and business performance) if it is well planned and implemented when the philosophicalquality aspects of the organisation are coupled with employee training, periodic audits, correctiveaction and commitment at all levels of the organisation.Originality/value – This paper’s unique contribution to the literature is the rigorous research andanalysis which statistically identify the best predictors for successful ISO 9000 implementation. Theresults demystify the confusion and contradictions which exist in the literature on the efficacy ofISO 9000 certification.